Antibiotic treatment of pneumonia and bronchiolitis. A prospective randomised study. Issue 11 (November 1984) - Friis, B; Andersen, P; Brenøe, E; Hornsleth, A; Jensen, A; Knudsen, F U; Krasilnikoff, P A; Mordhorst, C H; Nielsen, S; Uldall, P
Abstract : Routine administration of antibiotics in the treatment of pneumonia and bronchiolitis in infants and small children was evaluated in an open randomised prospective trial. From 1979-82 136 children between the age of 1 month and 6 years were allocated to one of two treatment groups shortly after their admission to a paediatric ward. Group A patients were to be given antibiotics but those in group B were not. None of the children had received antibiotics before hospital admission. A viral infection was diagnosed in 38 of the 72 patients from group A and in 34 of the 64 patients from group B. Respiratory syncytial virus was detected in 84% of these patients. Samples of tracheal secretions showed no differences between the groups in respect of cytology and bacterial flora. Nor were there any significant differences in the course of acute disease, the frequency of fever relapse and pulmonary complications. Fifteen patients from group B were subsequently treated with antibiotics: two of these developed secondary purulent infections of the middle ear and one showed a slight pleural effusion. These results do not support the routine use of antibiotics in infants and small children admitted to hospital with pneumonia and bronchiolitis.